Material editorial como herramienta de apoyo para las actividades dirigidas a los adultos mayores del centro gerontológico Vida a los años - Yanza Calva, Katherine Gissela (2024)
In Ecuador, the scant attention to studies on older adults has created a void of information and interest, as well as a lack of specialized material. This has resulted in the displacement of the needs and requirements of this population, marginalizing them in terms of comprehensive care. Recognizing aging as a stage of vulnerability, it is crucial to address it through comprehensive parameters and evaluations that ensure the physical and emotional well-being of older adults. The main goal of the ongoing project is the creation of editorial material aimed at supporting activities aimed at older adults in the "Life in Years" gerontological center. This initiative seeks to provide adequate stimulation to day center residents, thus improving their quality of life. The methodology adopted included background review, bibliographic research and observation. Material and activities were applied to the residents of the center, evaluating the effectiveness of said non-standardized elements. In addition, interviews were carried out with specialists to obtain an overview of the situation, generating criteria that contributed to the development of the prototype material. One of the main limitations identified in the proposal lies in the adaptation to the various cognitive abilities and individual preferences of users. The expected contributions of the project seek to promote active and enriching aging, promoting the quality of life of older adults and taking into account their specific needs and preferences. This comprehensive approach aims to fill the gap in care for this population in Ecuador.